Метод оптимізації портфелю проектів на основі метрик в умовах трансформації ІТ - Остахов, Володимир Вікторович; Морозов, Віктор Володимирович; Артикульна, Надія Францівна (НТУ "ХПІ", 2018)
У статті досліджуються причини необхідності застосування сучасних підходів до впровадження нових продуктів та послуг для клієнтів банківських установ, розглядаються підходи до оптимізації та переформатування портфелів проектів шляхом застосування метрик та ключових показників ефективності впровадження нових продуктів та послуг. На конкретних прикладах розглядаються ті метрики та показники ефективності, що в комплексі можуть значно скоротити витрати на впровадження нового функціоналу та збільшити фінансові надходження за рахунок своєчасності та якості продуктів та послуг для клієнта. Аналізується трансформація роботи ІТ підрозділів за рахунок оптимізації процесів в стратегії отримання максимального прибутку. Детально пояснюється тісний та комплексний взаємозв‘язок між системою метрик, які відображають оцінку поточних процесів впровадження продуктів та послуг, з встановленими цільовими показниками для ІТ підрозділу. Зроблено висновки про тренди метрик та показників технологічності по впровадженню ІТ проектів та їх вплив на розвиток банківського бізнесу та сфери в цілому. Окремо висвітлено питання щодо запровадження нових технологій та навіть цілих програмних комплексів, що визнані світовою банківської спільнотою для прискорення впровадження продуктів та послуг, і водночас орієнтованих на суттєві скорочення витрат з боку ІТ підрозділів.

The article explores the reasons for the need of applying modern approaches to implementation of new products and services for customers of banking institutions, examines approaches to optimizing and reformatting project portfolios by applying metrics and key performance indicators to the implementation of new products and services. With specific examples, those metrics and performance indicators that in the complex can significantly reduce the cost of implementing new functionality and increase financial returns due to the timeliness and quality of products and services for the client are envisaged. Transformation of work of IT departments is analyzed through optimization of processes in the strategy of obtaining maximum profit in terms of minimum required but sufficient investment in the bank‘s IT development. Close and integrated relationship between the system of metrics reflecting an assessment of current processes for implementing products and services and the established targets for IT department is explained in detail. In addition to the metric system, key indicators (KPIs) with established normative values are considered, interrelations between them are described and degree of their influence is analyzed, and their reciprocal complementation as an integrated system for measuring and improving processes of implementation of products and services is provided. Conclusions are made about trends in metrics and performance indicators for the implementation of IT projects and their impact on the development of banking business and the sphere as a whole. The issues of implementing new technologies and even whole software complexes that are recognized in the world by banking community for accelerating implementation of products and services, while simultaneously targeting significant cost reductions in the part of IT departments, are highlighted.
Method of project portfolio optimization based on metrics in the context of IT transformation .
Keywords: фінансовий ринок; банківська сфера; ІТ проект; ІТ ресурси; тренд; management; IT project; T resources; bank; trend